Interrogative Sentences In Torajanese And English: A Contrastive Study - Erin Natal; Sudirman Maca; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2022)
This study aims to identify the forms of interrogative sentences in Torajanese and English structurally. This research is a descriptive qualitative research with the sample of native speakers of Torajanese in Pangala’ Village, North Toraja Regency. The method used in this research is contrastive method proposed by Tarigan. Then, for analyzed the types and forms of interrogative sentence the writer used the theory proposed by Quirk. The results of this research indicated that there were dominant differences in terms of sentence structure between Torajanese and English. The first types is Yes/No question, there are 8 forms of Interrogative sentences in Torajanese. Then, for the second types there are 7 forms of Wh-question. In the third types namely Alternative question there are 3 forms. Moreover, the differences from both languages were in placing the question word, in English it always begins with an Auxiliary verb or To Be and Wh-word. While, in Torajanese it was “Raka” which was equal to auxiliary verb, In Torajanese, it did not always begin in front of the sentence, but begins in the middle, and at the end of the sentence.